Quaternary ZrCuCa-based thin films metallic glasses deposited by cathodic arc deposition - Parau, Anca Constantina; Dinu, Mihaela; Vitelaru, Catalin; Cotrut, Cosmin Mihai; Vranceanu, Diana Maria; (Dragomir), Alina Vladescu (Arabian journal of chemistry, 2023)
The current study’s aim is to obtain quaternary ZrCuCa based thin films using a physical vapor deposition method (PVD) - cathodic arc approach – in order to improve the surface properties of 316L stainless steel and Ti6Al4V implantable materials. The developed ZrCuCa-based layers could be potential candidates in the medical industry if they are able to combine their exceptional mechanical properties with the corrosion resistance of amorphous metallic glasses. Furthermore, addition of Mo, Mg, Si, and Sr was taken into consideration for the ZrCuCa structure and the resulted quaternary systems were analysed in detail, through electrochemical tests and bioactivity assay, which were carried out in synthetic body fluid (SBF) at human body temperature (37 °C). Surface morphology and roughness of the specimens before and after the tests were also evaluated. The results showed that regardless the substrate type, the roughness of the surface has increased for all coatings from 19 nm for 316L, and 50 nm for Ti6Al4V, to 2000 nm). The adhesion of obtained coatings was reached from 8 N to 18, the coatings on Ti6Al4V alloy was found to be from 12 N to 18 N, while on 316L steel was from 8 N to 15 N, indicating that the coatings deposited on Ti alloy have a better adhesion. The corrosion current density parameter for ZrCuCaMo and ZrCuCaMg sjowe the lowest value (316L: 21.99 µA/cm2 and 11.37 µA/cm2; Ti6Al4V: 1.62 µA/cm2 and 13.37 µA/cm2), indicating the best corrosion resistance. The mass evolution of the coatings deposited on 316L was ranged from the −0.47 mg to 1.37 mg, while for those deposited on Ti6Al4V, the values were ranged from −0.08 mg to 2.66 mg, indicating a degradation and biomineralization process, respectively. In conclusion, the electrochemical studies and bioactivity experiments demonstrated that the suggested coatings improve the substrate’s behaviour in simulated conditions, highlighting their potential as biomaterials.